Perancangan Dan Pengembangan Konten Vıdeo Promosı Dı Instagram Pada Umkm Tempat Makan Lo Ka Cıong Cıa Tang - Jimmy Pratama; Jacky Jacky (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
In today’s society, along with the development of technology and knowledge, there are many ways that can be used to promote a business. One way to promote a business that is currently on the trend is promotional media content through the Instagram application, which is also known as Instagram ads. Instagram ads are posts or Stories that a business buys to promote to users’ Instagram feeds. They can seem just like regular Instagram posts but are always marked by a “Sponsored” badge. With a potential audience of more than 928 million people, Instagram ads are a key tool for any social media marketer to market their business. The purpose of this research paper is to design promotional media content on Instagram at the MSME restaurant "Lo Ka Ciong Cia Tang". The focus of the research is on the Promotional and Advertising sector for MSME business in the regional area. The data source used in this study is the primary data source, which means the data is obtained directly from the researcher through various methods, mainly interviews and observations.Results of the study discuss the promotional video content’s impact on the MSME business. This study finds that promotional media content on Instagram does bring a realizable impact to the business. This can be seen from the increase in sales in the few months since the promotional video was held, and the gradual increase in ordering through the WhatsApp application. It is important to remember that the results of this study cannot be separated from the influence of the control factors used